The Lunar Chronicles: Scarlet - Book 2 - Meyer, Marissa (New York : Feiwel and Friends, 2013)
Scarlet Benoit and Wolf, a street fighter who may have information about her missing grandmother, join forces with Cinder as they try to stay one step ahead of the vicious Lunar Queen Levana in this story inspired by Little Red Riding Hood.
Keywords: Science fiction; Cyborgs -- Juvenile fiction; Missing persons -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Science fiction; Cyborgs -- Fiction; Missing persons -- Fiction; Extraterrestrial beings -- Fiction